Syzygium cumini Shelterbelt - Effect on Crop Yields - Sharma, K. K.; Kumar, Rajesh (Indian Forester, 1997)
A study was conducted to investigate the influence of 25 year old Syzygium cumini shelterbelt grown on north-south direction in single row on the growth and yield of Sorghum vulgare cultivated for fodder on western side of the belt. The results of the study show that mean green fodder yield, plant density and crop height were numerically lowest by 56.72 percent, 73.48 percent and 36.54 percent, respectively upto 5 m from tree belt as compared to the farthest plots located at 20.5 m distance in the open (control). Numerically higher values from these crop parameters were noted at later distances upto 8 m and beyond this uniform pattern’of growth and yield of S. vulgare was found. Therefore, it can be generalized that the impact oftree belt on Sorghum crop can be experienced upto 5 m, there is little impact upto 8 m distance and almost no impact beyond 8 m. The economic losses in green fodder yield in the affected area (220 m2) works out to 198.55 kg per 55 m tree line (one sided) are well compensated by the sale of timber harvested time to time by the farmer.